2008
DOI: 10.1088/0960-1317/18/9/095026
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative cooling of sessile water microdrops measured with atomic force microscope cantilevers

Abstract: We monitored the evaporation kinetics of drops from solid surfaces and the resulting cooling of the surfaces. To do this we deposited water drops with diameters smaller than 100 µm onto atomic force microscope (AFM) cantilevers. Due to the surface tension of the liquid, the Laplace pressure inside the drop, the change of the interfacial stress at the solid-liquid boundary and evaporative cooling, the cantilevers are deflected by typically some hundred nanometers. We used pure silicon and gold-coated silicon ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…with A the area of the liquid-air interface, q the average heat flux (∼2 kJ/s m 2 ), ρ the density of the fluid and H ν the vaporization enthalpy (2.27 × 10 6 J/kg and 8.41 × 10 5 J/kg for water and ethanol, respectively) [35][36][37], and take a meniscus length along the channel of about l = 5 μm. For the characteristic time τ for displacement of the meniscus over its length one finds then: τ = lρ · H ν /q ≈ 5 s and 2 s for water and ethanol, respectively.…”
Section: Determination Of Membrane Deflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…with A the area of the liquid-air interface, q the average heat flux (∼2 kJ/s m 2 ), ρ the density of the fluid and H ν the vaporization enthalpy (2.27 × 10 6 J/kg and 8.41 × 10 5 J/kg for water and ethanol, respectively) [35][36][37], and take a meniscus length along the channel of about l = 5 μm. For the characteristic time τ for displacement of the meniscus over its length one finds then: τ = lρ · H ν /q ≈ 5 s and 2 s for water and ethanol, respectively.…”
Section: Determination Of Membrane Deflectionmentioning
confidence: 99%
“…Further, we consider situations in which the length of the meniscus along the channel is smaller than, or in the order of the channel width w, which is the case in our experiments. Then the deflection in the elasticity problem is virtually independent of z and we are left with a quasi one-dimensional problem, the so-called cylindrical bending of a long rectangular plate [35]. It reads −κ∂ 4…”
Section: Analytical Modelingmentioning
confidence: 99%
“…During the latest years, Bonaccurso et al have made some studies on the transverse effect of a sessile droplet on the bending of a flexible microcantilever [36][37][38][39]. Recently, they studied the surface deformation of several tens micrometers-thick PDMS membrane with very low modulus induced by a sessile droplet using laser scanning confocal microscopy and estimated that the breadth of surface layer is approximately 16.0 nm by comparison between their experimental data and Rusanov's theoretical solution [17].…”
Section: Introductionmentioning
confidence: 99%
“…10. First, we suppose the droplet is ideally cylindrical [37] and the contact angle is θ . The wetted area is A = 2wa = 2wr sin θ , where r is the curvature radius of the water droplet.…”
Section: Cylindrical Droplet On MCLmentioning
confidence: 99%
“…Some researchers studied the influence of nanobubbles on the bending of MCLs [35,36]. Recently, Bonaccurso et al developed a FEM model for the bending of a cantilever and measured the bending versus time [37]. Zheng et al used the energy method to study the directional movement of liquid droplets on a microbeam with a varying or gradient stiffness and found that the droplet will move to the softer end of the beam [38].…”
Section: Introductionmentioning
confidence: 99%